Neurobehaviour of school age children born to diabetic mothers. Issue 2 (1st September 1998) - Ornoy, A; Ratzon, N; Greenbaum, C; Peretz, E; Soriano, D; Dulitzky, M
Abstract : AIM: To study the neurobehavioural effects that diabetes during pregnancy might have on children by school age. METHODS: The neurobehavioural function of 57 school age children born to 48, well controlled diabetic mothers was compared with 57 control children matched for age, birth order, and parental socioeconomic status, using several cognitive, behavioural, sensory and motor neurological tests. RESULTS: The IQ scores of the index group children were similar to those of control children (117.7±13.4 vs 118.5±10.1). There were no differences between the groups in various sensory motor functions. However, the index group children performed less well than the controls on indices of fine and gross motor functions, as observed on the Bruininks–Oseretzky test of motor proficiency. The scores of children born to diabetic mothers were higher than controls on the Touwen and Prechtl neurological examination. They also performed worse in the Pollack tapper test which is designed to detect minor neurological deficits, inattention, and hyperactivity. The index children had higher scores on the Conners abbreviated parent–teacher questionnaire which measures hyperactivity and inattention. There was a negative correlation between the performance of the index group children on various neurodevelopmental and behavioural tests and the severity of hyperglycaemia, as assessed by blood glycosylated haemoglobin and acetonuria. CONCLUSIONS: Diabetes during pregnancy adversely affects some fine neurological functions in children at school age, but not their cognitive scores. These effects are not correlated with the degree of glycaemic control.